Enhancing the Selectivity between Oxygen and Chlorine towards Chlorine during the Anodic Chlorine Evolution Reaction on a Dimensionally Stable Anode. Issue 12 (21st June 2019) - Wintrich, Daniela; Öhl, Denis; Barwe, Stefan; Ganassin, Alberto; Möller, Sandra; Tarnev, Tsvetan; Botz, Alexander; Ruff, Adrian; Clausmeyer, Jan; Masa, Justus; Schuhmann, Wolfgang
Abstract: The selectivity of the chlorine evolution reaction over the oxygen evolution reaction during the electrolysis of aqueous NaCl is, despite being very high, still insufficient to prevent expensive separation of the formed Cl2 and O2 by means of liquefaction. We hypothesize that, by decreasing the local activity of H2 O near the anode surface by substantially increasing the ionic strength of the electrolyte, the oxygen evolution reaction would be suppressed, leading concomitantly to a higher selectivity of Cl2 over O2 formation. Hence, the influence of the ionic strength on the competition between electrochemical evolution of O2 and Cl2 at dimensionally stable anodes (DSAs) was investigated. Addition of a high concentration of NaNO3, an inert electrolyte additive, increases the selectivity for chlorine at high current density, as determined by means of online electrochemical mass spectrometry and UV‐vis spectroscopy. We propose conditions in which free water is suppressed, owing to under‐coordination of the solvation shells of ions, as a general concept to modulate the selectivity of competing electrochemical reactions. Abstract : Healthy competition : The selectivity of the chlorine evolution reaction catalyzed by a dimensionally stable anode is influenced by the addition of sodium nitrate. By this, the parasitic oxygen evolution reaction is suppressed. This is shown by using online electrochemical mass spectrometry and UV‐Vis spectroscopy.